Project and operational stakeholders’ perspectives of an airport terminal project outcome / Nor Azlina Mohd Isa - Mohd Isa, Nor Azlina (2019)
An airport terminal development project is considered a complex project due to the large number of stakeholders involved in the development and the operations of the facility. The aviation industry evolution, especially in terms of its liberalisation, has also increased the complexity in terms of the synergy among the industry players. This study deliberated and examined the relationship between the critical success factors towards a successful project outcome, from a collective airport stakeholders’ perspective. The project chosen for this study was the development of the klia2 terminal which was completed and commissioned in May 2014. The project received huge coverage on its delay and cost overrun and as to this date, remains a controversial subject between the airport operator and the main user of the terminal. In collecting the perspectives of all airport stakeholders, two separate methods were used to suit the type of stakeholders. Stakeholders who belong to organisations were interviewed using the Project Implementation Profile (PIP) questionnaire while the klia2 passengers’ perspectives were obtained from the yearly Airport Service Quality (ASQ) Survey, conducted by the airport operator. Both data collections contain questions related to the drivers and the stakeholder satisfaction elements of the klia2 terminal, namely the project outcome. Using quota sampling, a total of 21 responses was obtained for the PIP, which was then analysed using non-parametric analysis.